Phenomenon of gold and diamond rushes as territorial, mining and socio-cultural development of continental spaces of South Africa (part IІ) - Gennadiy Gayko; Volodymyr Biletsky (Cхід, 2017)
This series of articles systematizes the events of settlement and economic development of vast spaces of North America, Australia, South Africa and North Asia, which are related to the movement of gold and diamond hunters (gold and diamond rushes). A chronological survey of the events is offered, the general phenomenon analyzed as well as specific aspects of its historical, mining, geological and organizational constituents covered. The material is divided into three separate but thematically united parts which describe the phenomenon of gold rush-spontaneous large-scale gold mining at newly discovered deposits in remote (for Europeans) parts of the world in the second half of the 19th century - the early 20th century.